Making Space for Painting - Paul Duro (Sillages Critiques)
Like the frame, the spaces of painting are constructions that factor into the (re)production of the limits of the pictorial world. How these spaces are viewed – when they are acknowledged as there at all – is largely overlooked in favor of a focus on the subject or “meaning” of the artwork, as if the key to understanding the image is to be found in the title – the starting point for the average gallery visitor’s apprehension of the artwork. This is perfectly legitimate, but it tends to distract the viewer from those parts of the work that are often considered less important, such as the background, as well as failing to account for the abstraction prevalent in the many modern artworks that avoid a title altogether. But space is never simply there; it is constructed like any other part of painting (line, color, composition etc.), and serves to situate the beholder within the domain of representation, positioning us in relation not only to the visual field (which is essentially the work of the frame), but also identifies these spaces according to the kinds of subject represented. The resulting field therefore opens up a world that functions, at its limit, symbolically, mediating between the beholder on the one hand and the needs of the artwork on the other. Presenting artwork drawn from cave painting to modernist abstraction, my examples seek to illustrate the various ways in which the framing of space may be said to be the foundational element of picture making – without which the limits of art could not be ascertained.